Ultrasonographic Findings in 41 Dogs Treated with Bone Marrow Aspirate Concentrate and Platelet-Rich Plasma for a Supraspinatus Tendinopathy: A Retrospective Study - McDougall, Renee A.; Canapp, Sherman O.; Canapp, Debra A. (Frontiers in Veterinary Science, 2018)
Objective To report sonographic findings for dogs with a supraspinatus tendinopathy (ST) treated with an ultrasound-guided intratendinous injection of bone marrow aspirate concentrate (BMAC) and platelet-rich plasma (PRP). Methods Medical records for dogs diagnosed with an ST and treated with a BMAC-PRP injection were reviewed. Data collected included patient signalment, radiographic findings at the time of initial evaluation, and sonographic findings, including cross-sectional area (CSA), fiber pattern, and echogenicity. Results Of 70 records reviewed, 41 met the inclusion criteria. Mean CSA of the supraspinatus tendon decreased by 0.06 cm2 between baseline and 45 days post-treatment (p = 0.0025), and 0.09 cm2 between baseline and 90 days post-treatment (p < 0.0001). Analysis of CSA in dogs with a unilateral ST at baseline revealed a difference of 0.08 cm2 between the affected and unaffected tendon at baseline, with the affected tendon measuring larger than the contralateral tendon (p < 0.0001). This difference became statistically insignificant by 45 days after treatment (u1-u0 = 0.04 cm2, p = 0.2855) and remained so 90 days post-treatment (u1-u0 = 0.03 cm2, p = 0.1910). In most cases (90.6%), the fiber pattern and echogenicity was considered improved 90 days post treatment. In a minority of these cases (13.8%) the fiber pattern and echogenicity abnormalities were considered resolved. Conclusions Using qualitative and quantitative sonographic measures, BMAC-PRP was associated with an improvement in supraspinatus tendon size, fiber pattern, and echogenicity. Given the protracted nature of tendon healing, long-term evaluation may reveal continued improvements in chronic structural changes not captured during the current study. Functional studies are required to evaluate the clinical benefits of BMAC-PRP in the treatment of STs in dogs. Clinical significance An ST is a common contributor to forelimb lameness in dogs and remains notoriously difficult to treat. Previous studies have been associated with inconsistent treatment outcomes. In the current study, BMAC-PRP is investigated as a minimally invasive treatment option, revealing positive sonographic results.